Local Wisdom of the Village Aceh Tamiang Regency in Conserving Water Resources - Nita, Arnita; Suciani, Ayu; Arnita; Daulay, Putri Agustin; Z, Soedirman; Rahmadi, M Taufik; Rosni, (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2023)
Water resources are an important element to meet the needs of living things. Water resources management efforts are needed so that water resources are maintained in their sustainability. In meeting their water needs, the community manages and uses water according to local wisdom. Local wisdom is an effort to preserve water and the environment. The purpose of this study was to analyze the forms of local wisdom that exist in Selamat village and to analyze the implementation of the community in preserving water resources. The methods in this study were qualitative, field observations, taking pictures and direct interviews. The results of this study are a form of local wisdom that prohibits tourists from visiting the Alur Batu waterfall, and closes the access road to the Alur Batu waterfall. The conclusion is the Selamat village community who do not want the stone groove to be used as a tourist spot by the government, thus closing the road access to the stone groove, and using the stone groove as a source of water. This research provides information to readers about the forms of local wisdom that exist in Selamat village. In this study, there are still shortcomings in obtaining data due to limited time, suggestions from the author for the next researcher to present more and more accurate data.